The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1088/0256-307x/30/8/085203
|View full text |Cite
|
Sign up to set email alerts
|

Laser Diagnostics of Combustion Enhancement on a CH 4 /Air Bunsen Flame by Dielectric Barrier Discharge

Abstract: We investigate plasma-assisted combustion for premixed CH4/air Bunsen flames. Dielectric barrier discharge (DBD) is employed to produce non-equilibrium plasma for combustion enhancement. The transient planar laser induced fluorescence (PLIF) technique of CH and OH radicals is used to image reaction zones for enhancement measurement, and the emission spectra of the Bunsen flame are monitored to explore the kinetics mechanism. From the drift of radicals in PLIF images, the quantitative enhancement of plasma on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…They confirmed that with the use of AC-DBDPA, flame length and soot formation were decreased. Shao-Hua et al 32 concentrated the activation of methane/air flame by using cylindrical AC-DBDPA. The transient OH/CH-PLIF imaging was recorded to acquire the physical appearance and its changes in the Bunsen flame.…”
Section: Introductionmentioning
confidence: 99%
“…They confirmed that with the use of AC-DBDPA, flame length and soot formation were decreased. Shao-Hua et al 32 concentrated the activation of methane/air flame by using cylindrical AC-DBDPA. The transient OH/CH-PLIF imaging was recorded to acquire the physical appearance and its changes in the Bunsen flame.…”
Section: Introductionmentioning
confidence: 99%